Data quality comparative model for data warehouse. - Sidi, Fatimah; Ramli, Abdullah; A. Jabar, Marzanah; Affendey, Lilly Suriani; Mustapha, Aida; Ibrahim, Hamidah (2012)
The growth of daily data and complexity in data warehouse with enhanced the information technology has created new challenges for information user. The demand for quality data has increase an awareness of the quality, reliable and accuracy of information in making fast and reliable decision-making. Nowadays, many organizations are depending on their resources in data warehouse. As that matter of fact, the qualities of data warehouse are greatly concern. The poor and error data will cause more trouble in data warehouse as data accessed from the same resources by the user. Here we present the systematic review comparative model to determine the data quality model as further research in our studies.